The The Importance of Elevated Basal 17-hydroxyprogesterone in the Diagnosis of Children with Congenital Adrenal Hyperplasia - Zdravković, Vera; Ješić, Maja; Miolski, Jelena; Pavlović, Sonja (Journal of Medical Biochemistry, 2025)
Introduction: Congenital adrenal hyperplasia (CAH) is characterized by a deficiency of 21α-hydroxylase causing a deficiency of cortisol and aldosterone and overproduction of 17-hydroxyprogesterone. The classic and non-classical forms of the disease present with signs of precocious puberty (PP) and accelerated body and bone growth. Elevated basal and stimulated 17-hydroxyprogesterone and genetic testing are crucial for confirming a definitive diagnosis.Aim: To determine the significance of elevated basal 17-hydroxyprogesterone in children with signs of precocious puberty in the final diagnosis of Congenital Adrenal Hyperplasia.Material and methods: A prospective study was conducted at the University Children's Clinic and the Institute of Molecular Genetics and Genetic Engineering in Belgrade from 2019 to 2024. The study involved 64 subjects of both sexes, aged up to 18 years, with precocious puberty, accelerated bone and body growth, elevated basal 17-hydroxyprogesterone, who were divided into two groups based on the presence/absence of pathogenic variants in the CYP21A2 gene. The anthropometric measures, skeletal maturation and hormone levels were compared between those two groups.Results: The research includes 64 subjects, divided into two groups, with confirmed CAH (30 subjects) and with PP as the control group (34 subjects). A statistically significant difference was shown in basal (p=0.000000807) and stimulated 17-hydroxyprogesterone (p= 0.0125), cortisol (p= 0.0148) and androstenedione (p= 0.014) in homozygous carriers of pathogenic variants in the CYP21A2 gene.Conclusion: Clinical and laboratory parameters such as precocious puberty and 17-hydroxyprogesterone may be significant hints to consider a carrier mutation for congenital adrenal hyperplasia.
Keywords: 17-hydroxyprogesterone, congenital adrenal hyperplasia, precocious puberty, CYP21A2 heterozygous, CYP21A2 gene.